Methyltrioxorhenium Catalysis in Nonconventional Solvents: A Great Catalyst in a Safe Reaction Medium - Crucianelli, Marcello; Saladino, Raffaele; De Angelis, Francesco (ChemSusChem, 2010)
The requirement that chemical processes are sustainabable, reflected in waste reduction and the use of safe reagents and reaction conditions, is becoming even more stringent as a result of pressure by society and governments to preserve the environment and protect human health. Catalysis offers numerous benefits related to green chemistry, including lowered energetic reaction requirements; catalytic, rather than stoichiometric, amounts of materials; increased selectivity; lowered consumption of processing and separation agents; and, in many cases, the use of less‐toxic compounds. Our research group has for a long time been studying methyltrioxorhenium in the oxyfunctionalization of different substrates, by using H2O2 or its urea‐hydrogen peroxide complex as the primary oxidant. In this Review paper we aim to provide a full literature account on the catalytic activity and selectivity of methyltrioxorhenium in the oxyfunctionalization reaction, either in nonconventional solvents or under solvent‐free conditions, with a particular emphasis on the use of ionic liquids as green reaction media. Oxyfunctionalization reactions with methyltrioxorhenium (MTO), one of the most‐studied organometallic rhenium derivatives, are the subject of this Review. A detailed account is given of the catalytic activity and selectivity of MTO in nonconventional solvents or under solvent‐free conditions, using H2O2 or urea‐hydrogen peroxide complex as primary oxidants.